Bionic nanoprobe as well as preparation method and application thereof

By combining microfluidic control technology and ultrasonic sound field, bionic nanoprobes with uniform morphology and size and high envelope efficiency were successfully prepared, which solved the problems of low envelope efficiency and poor particle uniformity in the prior art, and improved the detection performance of nanoprobes.

CN119881298APending Publication Date: 2025-04-25THE NAT CENT FOR NANOSCI & TECH NCNST OF CHINA
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510159072.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-13
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

In the prior art, the envelope efficiency of bionic nanoparticles is low, the particle size and structural uniformity are poor, and the processing process is complicated, which can easily damage the nanoprobe and affect the detection performance.

Method used

Using a method of combining microfluidic technology with ultrasonic sound field, the biofilm is mixed with the nucleic acid nanoprobe and passed into the microfluidic chip, and the biofilm is crushed and reassembled to coat the nanoprobe.

Benefits of technology

The efficient envelope of bionic nanoprobes is achieved, ensuring the uniformity of the morphology and size of the particles and high envelope efficiency, shortening the processing time, avoiding probe damage, and improving detection performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119881298A_ABST
    Figure CN119881298A_ABST
Patent Text Reader

Abstract

The invention discloses a bionic nanoprobe as well as a preparation method and application thereof. The method comprises the following steps: mixing a biological membrane and a nucleic acid nanoprobe, introducing the mixture into a micro-fluidic chip placed in ultrasonic water bath equipment, and collecting a solution introduced into the micro-fluidic chip, so as to obtain the bionic nanoprobe. According to the method disclosed by the invention, the biofilm-coated bionic nanoprobe with uniform morphology and size and high coating efficiency can be obtained. The method is simple, convenient and rapid to operate, is suitable for various biological membranes and probes, and can meet different detection requirements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of nanotechnology and relates to a bionic nanoprobe and a preparation method and application thereof. Background Art

[0002] Nanoprobes have been widely used in molecular imaging, biosensing, and disease screening due to their unique physical and chemical properties. Spherical nucleic acids are spherical nanoparticles formed by highly directional assembly of dense oligonucleotide molecules. As a new type of nanoprobe, they have excellent biocompatibility and high target recognition efficiency based on their multivalent structure. However, due to the lack of cell and tissue specificity, the application effect and scope of spherical nucleic acids in biomedical testing are limited.

[0003] By mimicking the natural structures in the body, such as coating the cell membrane or extracellular vesicle membrane on its surface, biomimetic nanoprobes can significantly improve their affinity with specific biological targets, thereby enhancing targeting specificity and metabolic stability. These characteristics make biomimetic nanoprobes show great application potential in biomedical research and biosensing.

[0004] At present, a variety of methods for preparing biofilm-coated nanoparticles have been reported, but they generally face problems such as complex operation and low coating efficiency. The co-extrusion method repeatedly squeezes nanoparticles and biofilms through a nanoscale porous membrane, using mechanical force to promote the fusion of nanoparticles and biofilms; the repeated freeze-thaw method promotes cell rupture and nanoparticle encapsulation by alternating low-temperature freezing and room-temperature thawing; the cell exocytosis method induces the exocytosis process after cells take up nanoparticles to form biofilm-coated nanoparticles; the electrotransfection method uses electric pulses to create instantaneous pores in the biofilm to encapsulate nanoparticles; the ultrasound method uses an ultrasonic probe to apply acoustic wave stress to the solution in the test tube, causing the biofilm to rupture and assemble with the nanoparticles. However, these methods are difficult to ensure the high efficiency of preparing particles and the uniformity of size and structure. In addition, the long-term processing process is prone to damage the nanoprobe, affecting its subsequent detection performance.

[0005] CN110743019A discloses a cell membrane bionic nanoprobe targeting lung adenocarcinoma tumors and its application, which is composed of the following two parts: 1) hydrophobic perfluorocarbon as a highly sensitive 19F-MRI probe, wrapped with polylactic acid-glycolic acid copolymer, and loaded with near-infrared fluorescent small molecule indocyanine green, which can be used for in vivo 19F-MRI / fluorescence / photoacoustic trimodal imaging, and has obvious photothermal conversion efficiency under near-infrared light irradiation; 2) extract lung adenocarcinoma tumor cell membrane modified perfluorocarbon polymer nanoparticles, use the natural adhesion factors and related functional proteins on the cell membrane surface, so that it can be used in vivo to have homologous targeting to tumors, and enhance the enrichment of the diagnostic and therapeutic nanoprobe in tumors. The bionic nanoprobe specifically targets lung adenocarcinoma tumors, can be used for lung adenocarcinoma tumor 19F-MRI / fluorescence / photoacoustic trimodal imaging, and can also use the strong near-infrared light absorption ability of indocyanine green for photothermal treatment of lung cancer.

[0006] Therefore, there is an urgent need to provide a method for preparing a bionic nanoprobe with high bionic nanoparticle coating efficiency and good uniformity of particle size and structure. Summary of the invention

[0007] In view of the shortcomings of the prior art and actual needs, the present invention provides a bionic nanoprobe and a preparation method and application thereof, combining microfluidics technology and ultrasonic acoustic field to prepare a bionic nanoprobe coated with a cell membrane or an extracellular vesicle membrane. The method of the present invention aims to solve the problems of low coating efficiency and poor uniformity of size and structure of bionic nanoparticles synthesized in the prior art, and shorten the processing time to avoid affecting the detection performance of the probe.

[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides a method for preparing a biomimetic nanoprobe, the method comprising: mixing a biofilm and a nucleic acid nanoprobe and passing the mixture into a microfluidic chip placed in an ultrasonic water bath device, and collecting the solution after passing into the microfluidic chip to obtain the biomimetic nanoprobe.

[0010] The method of the present invention successfully prepares biomimetic nanoprobes coated with biofilms with uniform morphology and size and high coating efficiency by combining microfluidic technology with ultrasonic sound field. It is a universal preparation method that can meet the diverse needs in the field of biomedical testing.

[0011] Preferably, the biological membrane comprises: a cell membrane and / or an extracellular vesicle membrane.

[0012] Preferably, the nucleic acid nanoprobe comprises double-stranded DNA and nanoparticles.

[0013] Preferably, the double-stranded DNA comprises an ATP nucleic acid aptamer and a reporter sequence modified with a fluorescent group.

[0014] Preferably, the fluorescent group includes Cy5.

[0015] Preferably, the double-stranded DNA comprises a modification group, and the modification group comprises a thiol group.

[0016] Preferably, the nanoparticles comprise gold nanoparticles.

[0017] Preferably, the microfluidic chip comprises an inlet, a double helix pipe and an outlet, the inlet has a length of 1.8-2.0 cm (e.g., 1.8 cm, 1.9 cm or 2.0 cm), a width of 250-350 μm (e.g., 250 μm, 280 μm, 300 μm or 350 μm), and a height of 40-60 μm (e.g., 40 μm, 42 μm, 44 μm, 50 μm, 55 μm or 60 μm).

[0018] Preferably, the double helix pipe has a length of 6.6-7.0 cm (e.g., 6.6 cm, 6.7 cm, 6.8 cm, 6.9 cm or 7.0 cm), a width of 250-350 μm (e.g., 250 μm, 280 μm, 300 μm or 350 μm), and a height of 40-60 μm (e.g., 40 μm, 42 μm, 44 μm, 50 μm, 55 μm or 60 μm).

[0019] Preferably, the pipe gap width of the double helix pipe is 400-600 μm (eg, 400 μm, 420 μm, 440 μm, 500 μm, 550 μm or 600 μm).

[0020] Preferably, the outlet has a length of about 0.3-0.5 cm (e.g., 0.3 cm, 0.4 cm or 0.5 cm), a width of 250-350 μm (e.g., 250 μm, 280 μm, 300 μm or 350 μm), and a height of 40-60 μm (e.g., 40 μm, 42 μm, 44 μm, 50 μm, 55 μm or 60 μm).

[0021] In the present invention, the preparation method of the microfluidic chip includes: mixing a high molecular polymer and a curing agent, pouring the mixture on a chip template after vacuum degassing, heating and curing, punching holes, connecting the mixture with a glass substrate after punching, and fixing a plastic pipe to obtain the microfluidic chip. The channel on the microfluidic chip in the present invention can be connected to a syringe pump device through a plastic pipe or the like.

[0022] Preferably, the mass ratio of the high molecular weight polymer to the curing agent is (5-15):1, for example, 5:1, 6:1, 7:1, 10:1, 12:1 or 15:1.

[0023] Preferably, the microfluidic chip is located at the bottom of the ultrasonic water bath equipment.

[0024] Preferably, the frequency of the ultrasonic water bath equipment is 75-85kHz (e.g., 75kHz, 76kHz, 78kHz, 80kHz, 82kHz or 85kHz), and the power is 90-110W (e.g., 90W, 92W, 94W, 96W, 100W, 105W or 110W).

[0025] Preferably, the ultrasonic intensity of the ultrasonic water bath equipment is 110-130 kPa (eg, 110 kPa, 112 kPa, 115 kPa, 120 kPa, 125 kPa or 130 kPa).

[0026] In the present invention, the biofilm is broken under the action of ultrasonic stress and quickly reassembled on the surface of the nanoprobe to form a bionic nanoprobe.

[0027] Preferably, the biofilm and nucleic acid nanoprobes are mixed and introduced into a microfluidic chip placed in an ultrasonic water bath at a flow rate of 8-10 mL / h (eg, 8 mL / h, 9 mL / h or 10 mL / h).

[0028] Preferably, collecting the solution after passing into the microfluidic chip includes taking the supernatant after centrifuging the solution, the centrifugation time is 0.5-2h (for example, 0.5h, 1h or 2h), and the centrifugal force is 8000-12000g (for example, 8000g, 9000g, 10000g, 11000g or 12000g).

[0029] In the present invention, the purpose of centrifugation is to effectively remove the excess biofilm in the supernatant and purify the prepared bionic nanoprobe.

[0030] In a second aspect, the present invention provides a bionic nanoprobe, which is prepared by the method for preparing a bionic nanoprobe described in the first aspect.

[0031] In a third aspect, the present invention provides the use of the bionic nanoprobe described in the second aspect in molecular imaging, biosensing or the preparation of disease detection products.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] (1) The biomimetic nanoprobe preparation method of the present invention mixes the biofilm and the nucleic acid nanoprobe and passes them into a microfluidic chip, which can quickly break up the biofilm within 0.5 seconds and reassemble it on the surface of the nanoprobe. The operation is simple, the size of the synthesized particle product is uniform, and the coating efficiency is high;

[0034] (2) The biomimetic nanoprobe preparation method of the present invention can achieve biofilm coating of more than 90% of particles by combining microfluidics technology and ultrasonic acoustic field, and has high repeatability and stability;

[0035] (3) The method of the present invention is applicable to the synthesis of biomimetic nanoprobes of various cell membranes and various extracellular vesicle membranes, and can be applied to different application scenarios by selecting biomembranes from different sources and different functional nucleic acid molecules;

[0036] (4) The present invention can synthesize bionic nanoprobes with corresponding cell, tissue, and target molecule specificity for different targets, and can develop bionic nanoprobes suitable for different needs. It is a universal preparation method that can meet the diverse needs in the field of biomedical testing. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 This is a structural diagram of a microfluidic chip used for synthesis of biomimetic nanoprobes according to the present invention;

[0038] Figure 2 Schematic diagram of preparing bionic nanoprobes using ultrasonic microfluidic chips in the present invention;

[0039] Figure 3 The transmission electron microscopy characterization results of AuNPs, SNA and 4T1 CCM-SNA prepared by the present invention are shown;

[0040] Figure 4 The size characterization results of AuNPs, SNA and 4T1 CCM-SNA prepared by the present invention are shown in FIG.

[0041] Figure 5 The surface potential characterization results of AuNPs, SNA and 4T1 CCM-SNA prepared by the present invention are shown in FIG.

[0042] Figure 6 This is the ATP test result diagram of CCM-SNA;

[0043] Figure 7 This is a transmission electron microscope characterization result diagram of the EM-SNA prepared by the present invention;

[0044] Figure 8 This is a diagram showing the size and surface potential characterization results of the 4T1 EM-SNA prepared in the present invention;

[0045] Fig. 9 This is a tumor cell-specific result diagram of EM-SNA;

[0046] Fig.10 This is the result of ATP detection by EM-SNA. DETAILED DESCRIPTION

[0047] To further illustrate the technical means and effects of the present invention, the present invention is further described below in conjunction with the embodiments and drawings. It should be understood that the specific implementation methods described herein are only used to explain the present invention, rather than to limit the present invention.

[0048] If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased through regular channels.

[0049] In order to more easily understand the present invention, some terms are first defined. As used in the present invention, unless otherwise defined, all technical terms and scientific terms used in the present invention have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. All patents and publications mentioned in the present invention are incorporated into the present invention in their entirety by reference.

[0050] The term "CCM" refers to cancer cell membrane.

[0051] The term "EM" refers to extracellular vesicle membrane.

[0052] The term "4T1" refers to a mouse breast cancer cell line.

[0053] The term "RAW 264.7" refers to a mouse monocytic macrophage leukemia cell line.

[0054] The term "MDA-MB-231" refers to a human breast cancer cell line.

[0055] The term "CT26" refers to a mouse colon cancer cell line.

[0056] The term "AuNPs" refers to gold nanoparticles.

[0057] The term "SNA" refers to spherical nucleic acid nanoprobe.

[0058] The term "CCM-SNA" refers to cancer cell membrane-coated spherical nucleic acid nanoprobes.

[0059] The term "EM-SNA" refers to extracellular vesicle membrane-coated spherical nucleic acid nanoprobes.

[0060] The term "PDMS" refers to polydimethylsiloxane.

[0061] Example 1

[0062] Preparation and characterization of CCM-coated SNA (CCM-SNA).

[0063] (1) Preparation of microfluidic chips

[0064] When making a microfluidic chip, PDMS (SYLGARD 184, purchased from DowCorning, USA) and a curing agent (SYLGARD 184, purchased from DowCorning, USA) were mixed at a mass ratio of 10:1, and after vacuum degassing, they were poured on a chip template (prepared using soft lithography technology) and heated and cured at 100°C for 20 minutes. Subsequently, a hole puncher was used to punch holes in the cured PDMS, which was connected to a glass substrate using a plasma cleaner, and a plastic pipe was fixed to the chip with a sealant, thereby completing the preparation of a microfluidic chip. The microfluidic chip includes an inlet, a double helix pipe and an outlet. The length of the inlet is 1.90 cm, the width is 300 μm, and the height is 50 μm; the length of the double helix pipe is 6.8 cm, the width is 300 μm, and the height is 50 μm. The pipe gap width of the double helix pipe is 500 μm, and the length of the outlet is 0.40 cm, the width is 300 μm, and the height is 50 μm. Figure 1 As shown, the channel on the microfluidic chip can be connected to the injection pump device through a plastic tube or the like.

[0065] (2) Collection of CCM

[0066] First, the cells were washed twice with PBS and then resuspended in a hypotonic buffer containing 20 mM Tris-HCl, 10 mM KCl, 2 mM MgCl2, and EDTA-free protease inhibitors and incubated for 1 h. Next, the cells were fully broken up with the help of a grinder and centrifuged at 10,000 g for 10 min to collect the supernatant and remove the cell debris. After that, the supernatant was centrifuged again, this time at 100,000 g for 1 h. After the centrifugation, the precipitate was collected and resuspended in PBS, and then extruded using an extruder, first with a 400 nm polycarbonate filter, then with a 100 nm filter, and repeated for a total of 8 times to obtain CCM. Finally, the obtained CCM was packaged and stored at -80 ° C for subsequent use.

[0067] The concentration and size distribution of the CCM obtained above were characterized using a nanoparticle tracking analyzer.

[0068] (3) Preparation of SNA nanoprobes

[0069] First, 15 nm gold nanoparticles were synthesized by reducing HAuCl4 with citric acid. 8 M -1 cm -1) and the gold nanoparticle solution absorb at 524nm, and the gold nanoparticle concentration is calculated according to the Lambert-Beer rule. TCEP is used to reduce 100μM thiol-modified DNA sequence at room temperature. 10nM AuNPs and 3μM thiol-modified double-stranded DNA, double-stranded DNA is hybridized by ATP nucleic acid aptamer SEQ ID NO.1: HS-TTTTTACCTGGGGGAGTATTGCGGAGGAAGGT and Cy5 fluorescent group modified reporter sequence SEQ ID NO.2 (ACCTTCCTCCGCAATACT-Cy5) and mixed evenly, and then placed in -20℃ freezer for 2h. After thawing, use washing buffer (25mM HEPES, 100mM NaCl, pH=7.6) and ultrafiltration tube (100kDa) 6000g, 3min centrifugation to wash 3 times, resuspend with PBS to obtain SNA nanoprobe, and store at 4℃ for use.

[0070] (4) Preparation and characterization of CCM-coated SNA (CCM-SNA), as shown in the schematic diagram Figure 2 shown.

[0071] 10 nM SNA was mixed with 8 × 10 10 / mL of 4T1 CCM was fully mixed and then passed into the microfluidic chip placed at the bottom of the ultrasonic water bath at a flow rate of 10mL / h. The frequency of the ultrasonic water bath was 80kHz and the power was 100W. The synthesized 4T1 CCM-SNA was centrifuged at a centrifugal force of 10000g for 1h to remove excess CCM in the supernatant.

[0072] Transmission electron microscopy was used to characterize the particle morphology and size distribution. Figure 3 As shown, the prepared 4T1 CCM-SNA has a uniform size distribution. Compared with bare AuNPs and SNA, 4T1CCM-SNA exhibits clear core-shell structural characteristics, and the coating efficiency of CCM on the probe is about 93%.

[0073] Dynamic light scattering characterization Figure 4 As shown in Figure 2, the average size of AuNPs is about 16.9 nm. After AuNPs are modified with DNA sequences to form SNA, their size increases to 21.2 nm. After further coating with CCM, the size of the formed CCM-SNA increases to 25.1 nm. In addition, the average surface potential of the nanoparticles at these different stages is shown in Figure 2. Figure 5As shown: AuNPs is -23.7mV, SNA is -20.5mV, and CCM-SNA is -15.3mV. The above results prove that the method of the present invention can be used to prepare CCM-coated bionic nanoprobes. In the absence of ATP, the fluorescence signal of the Cy5 group of the probe reporter sequence close to the gold particle surface is quenched. When ATP is present, it binds to the nucleic acid aptamer and releases the reporter sequence, resulting in the recovery of the fluorescence signal. The prepared CCM-SNA was incubated with 0-8mM ATP solution, as shown in FIG. Figure 6 As shown, the probe can detect ATP in a concentration-dependent manner. The signals of the 4mM ATP group and the 8mM ATP group are 4.6 and 5.6 times higher than those of the 0mM ATP group, respectively, proving that the encapsulated probe can respond to ATP. CCM-SNA exhibits stronger targeting specificity. The CCM-SNA-based ATP detection system is conducive to the specific measurement of tumor cell ATP.

[0074] Example 2

[0075] Preparation and characterization of EM-coated SNA (EM-SNA).

[0076] (1) Preparation of microfluidic chips

[0077] When making the microfluidic chip, PDMS (SYLGARD 184, purchased from DowCorning, USA) and curing agent (SYLGARD 184, purchased from DowCorning, USA) were mixed in a mass ratio of 10:1, poured on a chip template (prepared by soft lithography technology) after vacuum degassing, and heated and cured at 100°C for 20 minutes. Subsequently, a hole is punched in the cured PDMS using a puncher, and the PDMS is connected to a glass substrate using a plasma cleaning machine. The plastic pipe is fixed to the chip using a sealant, thereby completing the preparation of a microfluidic chip. The microfluidic chip includes an inlet, a double helix pipe and an outlet. The inlet has a length of 1.80 cm, a width of 250 μm and a height of 40 μm; the double helix pipe has a length of 6.60 cm, a width of 250 μm and a height of 40 μm. The pipe gap width of the double helix pipe is 400 μm, the outlet has a length of 0.30 cm, a width of 250 μm and a height of 40 μm, and the channel on the microfluidic chip can be connected to an injection pump device through a plastic tube or the like.

[0078] (2) Collection of EM

[0079] When 4T1 cells, RAW264.7 cells, MDA-MB-231 cells, and CT26 cells grew to more than 70% abundance, their culture medium was collected. The collected culture medium was centrifuged at a centrifugal force of 2000g for 10 minutes, and this operation was repeated twice to completely remove the cell debris. Subsequently, the supernatant culture medium was taken and centrifuged at a centrifugal force of 10000g for 1 hour. After the centrifugation, the supernatant was filtered through a 0.22μm filter membrane to further remove impurities. After that, the filtered supernatant was centrifuged at a centrifugal force of 100000g for 3 hours using an ultracentrifuge. After the centrifugation was completed, the precipitated EM was gently resuspended and recovered using a PBS solution precooled at 4°C. Finally, the recovered EM samples were aliquoted and stored at -80°C for subsequent use.

[0080] The EM obtained above was characterized by a nanoparticle tracking analyzer for its concentration and size distribution.

[0081] (3) Preparation of SNA nanoprobe (refer to Example 1).

[0082] (4) Preparation and characterization of EM-coated SNA (EM-SNA)

[0083] 10 nM SNA was mixed with 8 × 10 10 / mL of 4T1 EM was fully mixed and then passed into the microfluidic chip placed at the bottom of the ultrasonic water bath at a flow rate of 10mL / h. The frequency of the ultrasonic water bath was 80kHz and the power was 100W. The synthesized 4T1 EM-SNA was centrifuged at a centrifugal force of 10000g for 1h to remove excess EM in the supernatant.

[0084] Transmission electron microscopy was used to characterize the particle morphology and size distribution. Figure 7 As shown in Figure 2, 4T1EM-SNA exhibits a distinct core-shell structure, and the coating efficiency of EM on the probe is about 95%. Figure 7 As shown, using EM from other cell lines (RAW 264.7, MDA-MB-231, CT26), the optimized concentration ratio was 10 nM SNA and 8 × 10 10 / mLEM, EM-SNA with obvious core-shell structure was successfully prepared, and the encapsulation efficiency was greater than 90%. The size and surface potential were characterized by dynamic light scattering. Figure 8 As shown, the average particle size of 4T1 EM-SNA is 26.9 nm, and the average surface potential is -12.5 mV. The above results prove that the method of the present invention can be used to prepare EM-coated biomimetic nanoprobes and has universal applicability to a variety of membranes.

[0085] 1 nM CT26 EM-SNA or SNA (probe labeled with Cy5 fluorescent group) was incubated with CT26 tumor cells or RAW 264.7 macrophages at 37°C for 4 h. Fig. 9 As shown in the figure, compared with SNA, the tumor cell uptake of CT26 EM-SNA was enhanced by 1.98 times, while the macrophage uptake was reduced by 1.88 times, indicating that the encapsulated probe has tumor cell specificity and immune escape ability.

[0086] In the absence of ATP, the fluorescence signal of the Cy5 group of the probe reporter sequence is quenched when it is close to the gold particle surface. When ATP is present, it binds to the aptamer and releases the reporter sequence, resulting in the recovery of the fluorescence signal. The prepared EM-SNA was incubated with 0-8mM ATP solution, such as Fig.10 As shown, the probes can detect ATP in a concentration-dependent manner, and the signals of the 4mM ATP group and the 8mM ATP group are 4.9 and 6.3 times higher than those of the 0mM ATP group, respectively, proving that these coated probes can respond to ATP.

[0087] Example 3

[0088] Preparation and characterization of CCM-coated SNA (CCM-SNA).

[0089] (1) Preparation of microfluidic chips

[0090] When making the microfluidic chip, PDMS (SYLGARD 184, purchased from DowCorning, USA) and curing agent (SYLGARD 184, purchased from DowCorning, USA) were mixed in a mass ratio of 10:1, poured on a chip template (prepared by soft lithography technology) after vacuum degassing, and heated and cured at 100°C for 20 minutes. Subsequently, a hole is punched in the cured PDMS using a puncher, and the PDMS is connected to a glass substrate using a plasma cleaning machine. The plastic pipe is fixed to the chip using a sealant, thereby completing the preparation of a microfluidic chip. The microfluidic chip includes an inlet, a double helix pipe and an outlet. The inlet has a length of 2.0 cm, a width of 350 μm and a height of 60 μm; the double helix pipe has a length of 7.00 cm, a width of 350 μm and a height of 60 μm, a pipe gap width of the double helix pipe is 600 μm, and the outlet has a length of 0.50 cm, a width of 350 μm and a height of 60 μm. The channel on the microfluidic chip can be connected to an injection pump device through a plastic tube or the like.

[0091] (2) Collection of CCM (see Example 1).

[0092] (3) Preparation of SNA nanoprobe (refer to Example 1).

[0093] (4) Preparation and characterization of CCM-coated SNA (CCM-SNA)

[0094] 10 nM SNA was mixed with 8 × 10 10 / mL of 4T1 CCM was fully mixed and then passed into the microfluidic chip placed at the bottom of the ultrasonic water bath at a flow rate of 8mL / h. The frequency of the ultrasonic water bath was 80kHz and the power was 100W. The synthesized 4T1 CCM-SNA was centrifuged at a centrifugal force of 12000g for 1h to remove excess CCM in the supernatant.

[0095] Transmission electron microscopy was used to characterize the particle morphology and size distribution. Results The prepared 4T1CCM-SNA had a uniform size distribution, and compared with bare AuNPs and SNA, 4T1 CCM-SNA showed clear core-shell structural characteristics, and the coating efficiency of CCM on the probe was about 92%.

[0096] The average size of AuNPs is about 16.9nm. After AuNPs are modified with DNA sequences to form SNA, their size increases to 21.2nm. After further coating with CCM, the size of the formed CCM-SNA increases to 25.1nm. In addition, the average surface potential results of the nanoparticles at these different stages are: AuNPs is -23.7mV, SNA is -20.5mV, and CCM-SNA is -15.3mV. The above results prove that the method of the present invention can be used to prepare CCM-coated bionic nanoprobes. In the absence of ATP, the fluorescence signal of the Cy5 group of the probe reporter sequence close to the surface of the gold particle is quenched. When ATP is present, it binds to the nucleic acid aptamer and releases the reporter sequence, resulting in the recovery of the fluorescence signal. The prepared CCM-SNA is incubated with a 0-8mM ATP solution, and the probe can detect ATP in a concentration-dependent manner. The signals of the 4mMATP group and the 8mMATP group are 4.6 and 5.6 times higher than those of the 0mMATP group, respectively, proving that the encapsulated probe can respond to ATP.

[0097] Example 4

[0098] The difference between this embodiment and embodiment 1 is that in step (1), the inlet of the microfluidic chip has a length of 0.4 cm, a width of 300 μm, and a height of 50 μm.

[0099] Results: When the inlet channel length of the microfluidic chip is short, the coating efficiency will be affected, and the uniformity and stability of the coating process will also be reduced.

[0100] Example 5

[0101] The difference between this embodiment and embodiment 1 is that in step (1), the length of the double helix channel of the microfluidic chip is 3.4 cm and the width is 300 μm.

[0102] Results: When the length of the double helix channel of the microfluidic chip is short, the coating efficiency will be affected, and the uniformity and stability of the coating process will also be reduced.

[0103] Example 6

[0104] The difference between this embodiment and embodiment 1 is that in step (4), the microfluidic chip is located in the middle of the ultrasonic water bath device.

[0105] Results: CCM-SNA with core-shell structure could be synthesized, but the encapsulation efficiency was lower than that when the microfluidic chip was placed at the bottom position of the ultrasonic water bath device.

[0106] Example 7

[0107] The difference between this example and Example 1 is that the flow rate of SNA and 4T1 CCM in step (4) is 5 mL / h.

[0108] Results: The core-shell CCM-SNA could be synthesized, but the encapsulation efficiency was lower than that at a flow rate of 10 mL / h.

[0109] Example 8

[0110] The difference between this example and Example 1 is that the flow rate of SNA and 4T1 CCM in step (4) is 20 mL / h.

[0111] Results: The core-shell CCM-SNA could be synthesized, but the encapsulation efficiency was lower than that at a flow rate of 10 mL / h.

[0112] Example 9

[0113] The difference between this embodiment and embodiment 1 is that the frequency of the ultrasonic water bath equipment in step (4) is 80 kHz and the power is 50 W.

[0114] Results: The core-shell CCM-SNA could be synthesized, but the encapsulation efficiency was lower than that at a power of 100 W.

[0115] Comparative Example 1

[0116] The difference between this comparative example and Example 1 is that the mixed solution does not pass through the microfluidic chip, and the mixed solution of SNA and 4T1CCM is directly subjected to ultrasound. The ultrasound condition parameters refer to Example 1.

[0117] Results: Although the core-shell structured CCM-SNA could be synthesized by ultrasonic treatment of the mixed solution alone, the pressure generated by the acoustic field in the test tube was weaker and the membrane rupture efficiency was low, resulting in low encapsulation efficiency.

[0118] Comparative Example 2

[0119] The difference between this comparative example and Example 1 is that the mixed solution is not subjected to water bath ultrasound, and the SNA and 4T1 CCM mixed solution passing through the microfluidic chip is directly collected for centrifugation and detection. The centrifugation condition parameters refer to Example 1.

[0120] Result: Without ultrasound, the membrane cannot be broken and nanoparticles with core-shell structure cannot be synthesized.

[0121] In summary, the method of the present invention is simple and rapid to operate, is applicable to a variety of biofilms and probes, can meet different detection requirements, and can obtain biofilm-coated biomimetic nanoprobes with uniform morphology and size and high coating efficiency.

[0122] The applicant declares that the present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a biomimetic nanoprobe, characterized in that: The method comprises: mixing the biofilm and the nucleic acid nanoprobe and then passing the mixture into a microfluidic chip placed in an ultrasonic water bath device, and collecting the solution after passing into the microfluidic chip to obtain the bionic nanoprobe.

2. The method for preparing a biomimetic nanoprobe according to claim 1, characterized in that: The biological membrane includes: a cell membrane and / or an extracellular vesicle membrane.

3. The method for preparing a biomimetic nanoprobe according to claim 1 or 2, characterized in that: The microfluidic chip comprises an inlet, a double helix pipe and an outlet, wherein the inlet has a length of about 1.8-2.0 cm, a width of 250-350 μm, and a height of 40-60 μm; Preferably, the double helix pipe has a length of about 6.6-7.0 cm, a width of 250-350 μm, and a height of 40-60 μm; Preferably, the pipe gap width of the double helix pipe is 400-600 μm; Preferably, the outlet has a length of about 0.3-0.5 cm, a width of 250-350 μm, and a height of 40-60 μm.

4. The method for preparing a biomimetic nanoprobe according to any one of claims 1 to 3, characterized in that: The microfluidic chip is located at the bottom of the ultrasonic water bath equipment.

5. The method for preparing a biomimetic nanoprobe according to any one of claims 1 to 4, characterized in that: The frequency of the ultrasonic water bath equipment is 75-85kHz, and the power is 90-110W.

6. The method for preparing a biomimetic nanoprobe according to any one of claims 1 to 5, characterized in that: The ultrasonic intensity of the ultrasonic water bath equipment is 110-130 kPa.

7. The method for preparing a biomimetic nanoprobe according to any one of claims 1 to 6, characterized in that: The biofilm and nucleic acid nanoprobes are mixed and introduced into a microfluidic chip placed in an ultrasonic water bath device at a flow rate of 8-10 mL / h.

8. The method for preparing a biomimetic nanoprobe according to any one of claims 1 to 7, characterized in that: The collecting of the solution after passing into the microfluidic chip includes taking the supernatant after centrifuging the solution, the centrifugation time is 0.5-2h, and the centrifugal force is 8000-12000g.

9. A bionic nanoprobe, characterized in that: The bionic nanoprobe is prepared by the method for preparing a bionic nanoprobe according to any one of claims 1 to 8.

10. Use of the bionic nanoprobe according to claim 9 in molecular imaging, biosensing or preparation of disease detection products.

Citation Information

Patent Citations

  • Cell membrane bionic nanoprobe targeting lung adenocarcinomas and application of cell membrane bionic nanoprobe

    CN110743019A